A scalable, high-performance grouping DCF for the MAC layer enhancement of 802.11n. (1st January 2011) - Ting, K-C.; Lee, H-C.; Lai, Feipei
Today's 802.11 wireless local area network (WLAN) technology has become a popular protocol for internet access. However, this technology is not scalable at all because its capacity will deteriorate with an increase in the number of active stations, due to the huge collision costs involved. In this article, we propose a scalable, high performance grouping distributed coordination function (HG-DCF) which introduces the TDMA concept to partition all active stations into several groups to prevent all stations from transmitting frames simultaneously and to reduce the heavy overhead and increase the MAC layer efficiency of legacy DCF. Our analysis shows that the capacity (MAC layer efficiency) of our HG-DCF could reach 21.7%, which is 14% larger than that of the legacy DCF of 802.11n based on the parameters listed in Table 1. This improvement can be up to (21.7-7.7) / 7.7% = 183% and can be (21.7-13.4) / 13.4% = 61% improvement compared with that of theoretical DCF limit.